2022
DOI: 10.3390/ijms23073536
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into the Mode of Action of Acid β-Glucosidase Enhancer Ambroxol

Abstract: Ambroxol (ABX) is a mucolytic agent used for the treatment of respiratory diseases. Bioactivity has been demonstrated as an enhancement effect on lysosomal acid β-glucosidase (β-Glu) activity in Gaucher disease (GD). The positive effects observed have been attributed to a mechanism of action similar to pharmacological chaperones (PCs), but an exact mechanistic description is still pending. The current study uses cell culture and in vitro assays to study the effects of ABX on β-Glu activity, processing, and sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…Furthermore, due to a link of GCase activity and alpha-Synuclein accumulation ( 27 ), analysis of this neurodegenerative marker might provide important insights into the response of the central nervous system to ambroxol. All these findings are in accordance with a recent paper by Pantoom et al who suggest that ambroxol does not solely act as a pharmacological chaperone but also has additional modes of action ( 28 ).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, due to a link of GCase activity and alpha-Synuclein accumulation ( 27 ), analysis of this neurodegenerative marker might provide important insights into the response of the central nervous system to ambroxol. All these findings are in accordance with a recent paper by Pantoom et al who suggest that ambroxol does not solely act as a pharmacological chaperone but also has additional modes of action ( 28 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our proposal for FD is even more promising when considering that combined therapeutic approaches for rare diseases have been proposed [ 100 , 101 , 102 , 103 , 104 ] and that most importantly, one of them was recently approved by the FDA for the treatment of cystic fibrosis [ 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, because ambroxol's effects also include inhibition of pH-neutral, nonlysosomal glucocerebrosidase (GBA2), sodium channel blockade, upregulation of intracellular antioxidant and antiapoptotic signaling pathways, and antiinflammatory and immunomodulatory effects, it is uncertain to what extent reported improvements in neurological manifestations in children with GD3 are solely a function of lysosomal GCase activity enhancement. 4 Regarding ambroxol and GD1, although the safety profile seems favorable, clinical responses reported by Zhan et al 1 and Istaiti et al, 7 albeit in very different populations, appear less robust than those reported for ERTs and eliglustat. Perhaps a disconnect exists between the reported good neurological responses and the middling systemic responses, as hinted at in a recent case report 8 in which an infant with type 2 GD who started ambroxol shortly after birth had no neurological progression after 4 years yet had rapid systemic progression requiring institution of ERT.…”
Section: + Related Articlementioning
confidence: 94%
“…For GD, although several potential GCase chaperone molecules have been identified by computational modeling studies over the last several years, only 1 molecule, isofagamine, an iminosugar competitive inhibitor that binds GCase in the ER and dissociates in the lysosome, has undergone clinical trial. Despite encouraging preclinical and human cell culture results showing enhanced intracellular enzyme activity, a trial of a small number of patients failed to show a meaningful clinical benefit. Migalastat for Fabry disease (α-galactosidase deficiency) is the only approved pharmacological chaperone for a lysosomal storage disease and is effective only for specific amenable variants.…”
mentioning
confidence: 99%
See 1 more Smart Citation